A Substellar Companion to a Hot Star in K2's Campaign 0 Field. (10th October 2019) - Dholakia, S.; Dholakia, S.; Cody, Ann Marie; Howell, Steve B.; Johnson, Marshall C.; Isaacson, Howard; Everett, Mark E.; Ciardi, David R.; Howard, Andrew W.; Shporer, Avi
Abstract: The K2 mission has enabled searches for transits in crowded stellar environments very different from the original Kepler mission field. We describe here the reduction and analysis of time series data from K2 's Campaign 0 superstamp, which contains the 150 Myr open cluster M35. We report on the identification of a substellar transiting object orbiting an A star at the periphery of the superstamp. To investigate this transiting source, we performed ground based follow-up observations, including photometry with the Las Cumbres Observatory telescope network and high resolution spectroscopy with Keck/High Resolution Echelle Spectrometer. We confirm that the host star is a hot, rapidly rotating star, precluding precision radial velocity measurements. We nevertheless present a statistical validation of the planet or brown dwarf candidate using speckle interferometry from the WIYN telescope to rule out false positive stellar eclipsing binary scenarios. Based on parallax and proper motion data from Gaia Data Release 2 (DR2), we conclude that the star is not likely to be a member of M35, but instead is a background star around 100 pc behind the cluster. We present an updated ephemeris to enable future transit observations. We note that this is a rare system as a hot host star with a substellar companion. It has a high potential for future follow-up, including Doppler tomography and mid-infrared secondary transit observations.